(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Advances in science and technology have made it possible to obtain electricity from wind power. Although the work in this regard was started in the last century, the world is paying more attention to the construction of wind power plants. Wind power is currently being produced in 55 countries. In this regard, the work carried out in European countries is particularly noteworthy. The use of wind energy has already become an important branch of the energy sector. Among the CIS countries, measures are being taken to increase the production of electricity from wind power in the Republic of Belarus.